Key to successful legislation on the role of professional commitment, organizational behavior and understanding of legislation - Hamdi, Hamdi; Ujianto, Ujianto; Sumiati, Sumiati (Edelweiss Applied Science and Technology, 2024)
This study aims to examine the effect of Professional Commitment (X1) and Organizational Citizenship Behavior (X2) on Legislative Function Performance (Y) through Legislative Function Understanding (Z) as a mediating variable among members of the South Kalimantan Provincial DPRD. The research method uses a quantitative design with mediation analysis. Data were collected from 117 DPRD member respondents using a questionnaire that was tested for validity and reliability. The results of the analysis showed that X2 did not have a significant effect on Y (p-value = 0.089), while X2 had a significant negative effect on Z (p-value = 0.000). On the other hand, X1 showed a significant negative effect on Y (p-value = 0.000), but was not significant on Z (p-value = 0.337). Legislative Function Understanding (Z) did not function as a mediator between X2 and Y (p-value = 0.882) and between X1 and Y (p-value = 0.905). These findings emphasize the importance of increasing the professional commitment of DPRD members and paying attention to organizational citizenship behavior in an effort to improve legislative performance, while also showing that understanding the legislative function does not strengthen the relationship between independent and dependent variables. Further research is needed to explore other factors that may affect legislative performance.